The Effect of Exclusive Breastfeeding on Stunting Toddlers: A Scoping Review - Putri, Rokhiyatul Maila; Sumardiyono, Sumardiyono; Andarini, Ismiranti (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Toddlers, defined as children under five in the early stages of development, experience rapid growth but are vulnerable to nutritional problems such as stunting. Stunting is characterized by a child's height being shorter than the normal standard for their age, resulting from long-term undernutrition, recurrent infectious diseases, and inappropriate feeding practices. Exclusive breastfeeding is an important measure to prevent stunting, as breast milk provides the complete micronutrients and macronutrients necessary for optimal growth and development. Objective: The purpose of this study was to determine the effect of exclusive breastfeeding on stunting in toddlers. Method: The research design employed a scoping review approach, following the PRISMA-ScR flowchart. Articles were identified through searches on Google Scholar, PubMed, ScienceDirect, and the DOAJ database using keywords such as "effect" AND "giving" AND "exclusive breastfeeding" OR "stunted toddlers". The initial search yielded 821 articles, with six articles meeting the inclusion criteria for the final analysis. Result: The study found a significant relationship between exclusive breastfeeding (p-value=0.003) and the incidence of stunting in toddlers. Specifically, 75.9% of stunted toddlers and 67.2% of toddlers had not received exclusive breastfeeding. Conclusion: Exclusive breastfeeding affects the stunting in toddlers.